La prescripción en infracciones cometidas por adolescentes infractores, falencias en los tiempos de prescripción del ejercicio de la acción y medida socio-educativa. - Piedra Ochoa, Gabriel Alejandro (2023)
The Constitution of the Republic of Ecuador and our Ecuadorian legislation speak of the Right to Effective Judicial Protection, Personal Integrity, which guarantees that, in the event that an offence is committed against a person, this person has the security that there is due process so that the person responsible is assigned a penalty or socio-educational measure, as the case may be. The present research focuses on the lack of clarity regarding the time limits for offences committed by adolescent offenders within the Code for Children and Adolescents, specifically Article 334-A, bearing in mind that the normative system for these subjects of rights is governed by the best interests of the child or adolescent, through the administration of specialised justice. The lack of regulatory clarity in the statute of limitations mainly harms the victims and their own rights, as currently there is no differentiation between the statute of limitations for the exercise of the action in cases in which the judicial process has not yet begun and those in which it has already begun, times for counting the statute of limitations in continuous crimes, minimum statute of limitations periods, among other necessary aspects that should be applied within the law, which means that there is a disproportion between the rights that mostly benefits the adolescent offenders and harms the victims.